Avaliação do ciclo de vida - resenha histórica e perspetiva futura - Ferreira, José (2021)
Introduction: This article presents a historical review and future perspective of life cycle assessment (LCA), as a tool for environmental assessment of products. The first LCA studies, called REPA (Resource and Environmental Profile Analysis), were carried out in the United States of America (USA) in the early 70s of the last century and had as main motivation the aspects related to the environmental implications and the consumption of resources used in the packaging production. It was not until the mid-1980s that these studies began to be carried out in Europe through the Swiss Federal Laboratory for Testing and Investigating Materials (EMPA). Development: In the 90's there was a notable growth in LCA activities in Europe and the USA, namely in terms of harmonization of LCA methods and standardization activities carried out, respectively, by SETAC (Society of Environmental Toxicology and Chemistry) and ISO (International Organization for Standardization). As of the year 2000, countless international and regional organizations were created, with the objective of improving the credibility; acceptance and practice of LCA, as well as many computer tools (software and databases) were developed to support LCA studies. Conclusions: One of the main future challenges for LCA is its greater integration with other life cycle approaches, which have been emerged, as LCA studies have been increasingly well developed.